Triarylborane‐Catalyzed Alkenylation Reactions of Aryl Esters with Diazo Compounds. Issue 36 (15th July 2020) - Dasgupta, Ayan; Stefkova, Katarína; Babaahmadi, Rasool; Gierlichs, Lukas; Ariafard, Alireza; Melen, Rebecca L.
Abstract: Herein we report a facile, mild reaction protocol to form carbon–carbon bonds in the absence of transition metal catalysts. We demonstrate the metal‐free alkenylation reactions of aryl esters with α‐diazoesters to give highly functionalized enyne products. Catalytic amounts of tris(pentafluorophenyl)borane (10–20 mol %) are employed to afford the C=C coupled products (31 examples) in good to excellent yields (36–87 %). DFT studies were used to elucidate the mechanism for this alkenylation reaction. Abstract : 2 Become 1 : Lewis acidic boranes are employed in the metal‐free alkenylation reactions of aryl esters with α‐diazoesters to give highly functionalized alkene, enyne, and diene products in good to excellent yields. DFT studies have elucidated the mechanism for the reaction.